Le Canon 8 de Chénouté : d'après le manuscript Ifao Copte 2 et les fragments complémentaires - Shenute, Saint, approximately 348-466. (Bibliothèque d'études coptes ;, 2013)
Shenoute (4th-5th cent.), the abbot of the great monastery in Upper Egypt known as "White Monastery," is considered as the Coptic writer par excellence, being the author of nine books of so-called Canons, or sermons on monastic discipline. Scattered after their discovery in the late 1880's, like all manuscripts of the Monastery's library, the volumes have reached us only in a very fragmentary state. Canon 8 is a welcome exception, as a copy, dated 8th century and preserved up to 80%, has been kept in the collection of Ifao for over a hundred years. Presented here are the description, edition and translation of the various sermons contained in the manuscript, with colour reproductions of all the pages stored in Cairo. Such a valuable testimony should be of great interest to scholars in book history and Coptic language, as well as in Egyptian monasticism, which Shenoute, one of its most passionate representatives, served with a fiery and subtle rhetoric.